EKSEKUSI MATI DI INDONESIA (Perspektif Teori Hudud Muhammad Syahrur) - Hannani, Hannani (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2017)
Abstract: This paper will examine the execution of death in Indonesia with the view of Hudud Muhammad Syahrur Theory. The execution of the death penalty imposed by the Indonesian government on the law's injunction against death row inmates involved in serious crimes such as terrorist leader, narcotics producer. Death penalty is not enough to be seen from a positive-conceptual perspective, but it must go through a case-by-case approach, as each case has its own context and uniqueness. The death penalty to be the maximum sentence in the hudud theory of Muhammad Syahrur is called all-haddul a'la, and a minimum of one year's imprisonment as a minimum limit by Muhammad Syahrur is called al-haddul adnaa.